2022
DOI: 10.3390/jcm11030774
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Fractional CO2 Laser Therapy for Genitourinary Syndrome of Menopause in Breast Cancer Survivors

Abstract: (1) Background: The objective of this study was to determine the long-term efficacy of fractional CO2 laser therapy in breast cancer survivors. (2) Methods: This was a single-arm study of breast cancer survivors. Participants received three treatments of fractional CO2 laser therapy and returned for a 4 week follow-up. Participants were contacted for follow-up at annual intervals. The Vaginal Assessment Scale (VAS), the Female Sexual Function Index (FSFI), the Female Sexual Distress Scare Revised (FSDS-R), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…In total, 502 breast cancer survivors participated in the studies. The majority of studies [ 14 , 15 , 16 , 19 , 20 , 21 , 24 , 25 ] administered three cycles of vaginal laser treatment every 30 days; however, other approaches of laser administration were also used as the optimal number of cycles has yet to be defined.…”
Section: Therapeutic Options For Gsm In Breast Cancer Survivorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 502 breast cancer survivors participated in the studies. The majority of studies [ 14 , 15 , 16 , 19 , 20 , 21 , 24 , 25 ] administered three cycles of vaginal laser treatment every 30 days; however, other approaches of laser administration were also used as the optimal number of cycles has yet to be defined.…”
Section: Therapeutic Options For Gsm In Breast Cancer Survivorsmentioning
confidence: 99%
“…Four studies [ 16 , 23 , 24 , 25 ] evaluated the long-term sustainability of the improvement of GSM symptoms in breast cancer survivors, and the results are promising. Gambacciani et al [ 16 ] reported a maintained effect of laser therapy for at least 12 to 18 months.…”
Section: Therapeutic Options For Gsm In Breast Cancer Survivorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers are studying the biological effects of laser radiation with different wavelengths and using different biological objects of study [14,15]. The ability of light energy at different parameters of irradiation to either promote cell regeneration or initiate in them the occurrence of pathological changes due to the modulation of metabolic processes is of great interest [16,17].…”
Section: Introductionmentioning
confidence: 99%